The Effect of Customer Relationship Marketing and Service Quality on Customer Retention with Customer Satisfaction as A Mediating Variable In Forwarding Companies In Surabaya - Febriani Galih Saputro; Agus Dwi Sasono; Joko Suyono; Damarsari Ratnasahara Elisabeth; Abdul Thalib Bin Bonn (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: The aim of this study is to analyze the effect of customer relationship marketing and service quality on customer retention with customer satisfaction as a mediating variable in forwarding companies in Surabaya. Design/methodology/approach: The populations in this study are customers of forwarding companies in Surabaya and the sample in this study is 100 customers. The data analysis technique used was part analysis of linear regression. Findings: The research results are: 1) There is an effect of customer relationship marketing on customer retention at Forwarding Company in Surabaya, 2) There is an effect of service quality on customer retention at Forwarding Company in Surabaya, 3) There is an effect of customer relationship marketing on customer retention with customer satisfaction as a mediating variable at Forwarding Company in Surabaya, 4) There is an effect of service quality on customer retention with customer satisfaction as mediating variables at Forwarding Company in Surabaya, 5) There is an effect of customer relationship marketing on customer satisfaction at Forwarding Company in Surabaya, 6) There is an influence of service quality on customer satisfaction at Forwarding Company in Surabaya. Practical implications: The result of this research can be used as a reference in increasing customer retention with customer satisfaction. Paper type: Research paper